Experimental and discrete event simulation (DES) modeling analysis of the belt conveyor conveying capacity - Muas Muchtar; Muhammad Arsyad Suyuti; Syaharuddin Rasyid; Andi Saidah (Jurnal POLIMESIN, 2023)
Belt conveyors can continuously move the desired amount of material from one location to another. The conveying capacity of the conveyor must be met based on the previous design criteria. The belt conveyor must operate at the appropriate conveying speed and queue time interval. Higher or lower conveyor speeds and queue time intervals can cause a decrease in efficiency and productivity. The objectives of this study are 1) to determine the effect of the independent variables (observations), namely, the speed of the head pully conveyor and the time interval of the box queue, on the conveyor performance, 2) to obtain information on the normality profile and significance of the conveyor performance data. This research is oriented toward experimental and quantitative research designs. The independent variables observed are the speed of the head pully belt conveyor and the box queuing time interval on the dependent variable, namely the belt conveyor conveying capacity. The data collection technique is in the form of direct measurements on the conveyor system and the collection of output data from the previously designed DES modeling. Two types of analysis used are comparative quantitative analysis methods and statistical-based analysis. The results showed a significant influence between the independent variables of speed and box queue time interval on the conveying capacity of the belt conveyor. Another result is that the conveyor capacity data obtained from this study have a near-normal distribution and a high significance level.